Same-Family Cases of the Reincarnation Type in Japan - Ohkado, Masayuki (Journal of Scientific Exploration, 2017)
Dr. Ian Stevenson, the pioneer of the study of reincarnation phenomena, conjectures that the reason why a person is born in a particular family might be accounted for in terms of psychic connections: Shared experiences leave mental traces within us and produce psychic connections between the persons concerned and the longer an association between two persons lasts, and the greater its intensity, the stronger the connections between them become; such psychic connections act as an agent to attract a deceased person to be reborn to a particular person. This conjecture suggests that the most natural pattern of cases of the reincarnation type (CORT) is the one occurring within the same family since family members tend to develop such psychic connections most easily (Stevenson, 2001: 236-244). As Yanagida, who is known as the father of Japanese native folkloristics, reported skipped-generation reincarnation (grandparent to be reborn as grandchildren) might have been considered “normal” in some areas in prewar Japan (Yanagita, 2013). In Ohkado (2016a) I reported one same-family CORT occurring in contemporary Japan, suggesting that the phenomena are by no means obsolete. In the present article I would like to report another five same-family cases.